Efisiensi Pemasaran Komoditas Lada di Kabupaten Konawe Ditinjau Dari Perspektif Ekonomi Islam - Leni Saleh (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
The purpose of this study to determine the efficiency of the marketing of pepper inKonawe viewed from the perspective of Islamic economic. Method of sampling isdone by simple random sampling as many as 45 respondents out of the totalpopulation, while traders villages (PPD) were 3 people and traders districts(PPK) have as many as two people in the census.The result of the study conluded that the marketing efficiency of the in thevillage Unaasi. Anggaberi districts in Konawe through two (2) marketingchannels, namely :Marketing channel I, from farmers producing PPK ofinter-island trader, with the marketing margin 97,46 %. Marketing channel II,from farmers producing PPD PPK of inter-island trader, with themarketng margin 97,40%.From the analysis it can be conluded that the marketing activities on thecommodity pepper in Konawe already efficient, but needs to be improved. Interms of the service has been satisfactory. Viewed from the perspective of Islamiceconomy againts commodity pepper were done by farmers/producers, the views ofthe marketing is in conformity with the two assumptions that are under theinfluence of the spirit of Islam that is the assumption of economic rationality andselling without any coercion. Since marketing of commodities pepper is the effortsmade by farmers/producers in order to maximize satisfaction and fulfillment. Inmarketing the pepper that they (farmers) produced by choosing their ownmarketing channels they want to sell pepper production. Transactions conductedby this farmer also insyaAllah avoid speculative transactions, transactions that arenot clear (Gharar), usury and false (evil deeds).